Makna Setan dalam Antologi Cerpen “Arinillah” Karya Taufik Al-Hakim (Analisis Semiotik Carles Sanders Pirce) - Munawaroh; Susilawati, Ani (Uktub: Journal of Arabic Studies, 2023)
The أرني الله anthology is the work of Taufik El-Hakim with the theme of philosophy. In the short story anthology, there are three short stories had been researched, namely, الشهيد , وكانت الدنيا, and المرأة غلبت الشيطان. The three short stories have similarities, such as the emergence of personage devil with with different  characters, and the use of words and sentences have the shape of signs. Based on the uniqueness and the problem, the researcher reveals that the three short stories using Charles Sanders Pierc's Semiotic analysis knife. The method is descriptive qualitative method, the primary data source is the anthology of the short stories أرني الله by Taufik El-Hakim, and secondary data comes from books and other supporting articles. The research results are icons, indexes, and symbols which is  found in the three short stories, such as the word "in the Roma’s body" in the short story الشهيد which is an iconic sign from the word region or city. The sentence “They knelt except the devil. He looked at the miracle for a while, then turned his neck and shuddered and continued to heaven with a light walk" in the short story وكانت الدنيا which is an index sign of arrogance, and the word "Spring" in the short story المرأة غلبت الشيطان which is a symbol of prosperity. There are parallels The nature of the devil in the three short stories is the character of the protagonist and the character of the antagonist.